Polygonal examples in art education from point to line - ÖZCAN ÖZER, NERMİN (ELSEVIER SCIENCE BV, 2010)
In art education, the reciprocal relationship between lines and colours in art space is efficent elements for awakening art consciousness. Lines and colours complete themselves and build works of art in art space. In ths context, our problem is how elements of point, line and colour complete themselves and how they build references, in Department of Elementary Education, Ataturk Faculty of Education, Marmara University. Meaning and consistency of artistic concepts have great importance in education of individuals. Their ways of conception of these concepts affect their art consciousness in their lives. What they see where they look is related with their depth of thought. Their intelectual development reflects on esthetic realm as well. Our main aim is dealing with point, line and colour, and polygons in universe of design as means of education. Results of researchs made among students, related with art works based on polygons will be shown through a power-point presentation. Works made by students in field of line and colour will be exemplified, and dealt wih in an analytical and descriptive way. (C) 2010 Elsevier Ltd. All rights reserved
Keywords: Point; line; art; art education; geometry